Respuesta :

Answer:

x= -1 y= 6

Step-by-step explanation:

Solve equation [2] for the variable  y  

 [2]    3y = -2x + 16

 [2]    y = -2x/3 + 16/3

Plug this in for variable  y  in equation [1]

  [1]    9x - 2•(-2x/3+16/3) = -21

  [1]    31x/3 = -31/3

  [1]    31x = -31

Solve equation [1] for the variable  x  

  [1]    31x = - 31  

  [1]    x = - 1  

By now we know this much :

   x = -1

   y = -2x/3+16/3

Use the  x  value to solve for  y  

   y = -(2/3)(-1)+16/3 = 6  

Solution :

{x,y} = {-1,6}  

ACCESS MORE